The Influence Of Leader Member Exchange On Innovative Work Behavior With Perceived Organizational Support As A Mediation Variable To Grand Keisha Yogyakarta Hotel Employees - Saleh, Rr. Agidasyahna Winda; Probosari, Ninik (UPN Veteran Yogyakarta, 2024)
This abstract aims to investigate the influence of Leader Member Exchange (LMX) on innovative work behavior (IWB) with perceived organizational support (POS) as a mediating variable among employees of the Grand Keisha Hotel in Yogyakarta. The research problem focuses on the dynamics of the relationship between leaders and team members and how it influences the level of innovation in employee work behavior. The research method used was a survey with a questionnaire distributed to hotel employees. Data testing was carried out using statistical regression analysis techniques to measure the relationship between variables. The research results show that there is a significant positive relationship between LMX and IWB. In addition, POS also mediates the relationship between LMX and IWB. Thus, it can be concluded that the existence of a good relationship between leaders and team members (LMX) and perceived organizational support (POS) encourage an increase in innovative work behavior of hotel employees. These results provide important implications for management in improving leadership interactions with team members as well as strengthening organizational support to encourage innovation in the work environment.